HOW SOCIAL MEDIA AFFECT SOCIAL SKILL OF 2ND SEMESTER STUDENTS OF ENGINEERING FACULTY UNMAS DENPASAR PSDKU MATARAM IN ACADEMIC YEAR OF 2018/2019 - SEVENTILOFA, I GUSTI NGURAH OCTOVA (GANEC SWARA, 2019)
This study aims to find out whether social media can influence the social ability of the second semester students of the Faculty of Engineering of UNMAS Denpasar PSDKU Mataram, how social media can influence their social skills, whatever influences or changes that can be caused. This research is qualitative - explains the social phenomena that occur in society. The total sample is 15 second semester students of the faculty of engineering UNMAS Denpasar PSDKU Mataram. The method used to collect data is direct interview